Guidance for assessment of erythroderma in neonates and infants for the pediatric immunologist. Issue 3 (26th February 2019) - Ott, Hagen
Abstract: Neonatal and infantile erythroderma (NIE) represents the common clinical phenotype of heterogeneous diseases ranging from benign and transient skin conditions to fatal multiorgan disorders. NIE regularly demands a comprehensive diagnostic workup in a multiprofessional setting, especially if newborns and young infants with the disease develop a failure to thrive and concomitant infectious, neurologic, or metabolic complications. By obtaining a detailed medical history and performing a thorough clinical examination, targeted diagnostic steps can be scheduled for most affected children. If NIE occurs in the early neonatal period, lesional skin biopsy and histology are often indicated. Likewise, if monogenic skin or immunologic diseases are suspected, genetic testing with customized panels of potentially underlying genes is mandatory. Of note, if acute symptoms such as severe infections, metabolic acidosis, or seizures occur, rapid microbiologic and metabolic investigations are warranted to rule out immunodeficiency and inborn errors of metabolism.